2017
DOI: 10.1542/peds.2016-1870
|View full text |Cite
|
Sign up to set email alerts
|

NICU-based Interventions To Reduce Maternal Depressive and Anxiety Symptoms: A Meta-analysis

Abstract: Combined intervention effects significantly reduced maternal depressive but not anxiety symptoms. The evidence is strongest for the impact of cognitive behavioral therapy interventions on maternal depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 34 publications
7
69
0
6
Order By: Relevance
“…No prior review has comprehensively synthesized studies of interventions to reduce distress in NICU parents at large. Previous systematic reviews selected narrow scopes that limited their applicability across varied patient populations, treatment modalities, and psychological outcomes [20][21][22][23][24]. First, few reviews examined the effect of interventions on fathers' distress symptoms, even though NICU fathers experience birth-related psychological distress [25].…”
Section: Introductionmentioning
confidence: 99%
“…No prior review has comprehensively synthesized studies of interventions to reduce distress in NICU parents at large. Previous systematic reviews selected narrow scopes that limited their applicability across varied patient populations, treatment modalities, and psychological outcomes [20][21][22][23][24]. First, few reviews examined the effect of interventions on fathers' distress symptoms, even though NICU fathers experience birth-related psychological distress [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some interventions have been developed to reduce parental depression and anxiety in the NICU, such as educational content and therapy (42). These interventions have demonstrated that it is still unclear what is the best factor.…”
Section: Parent Characteristics and Perceived Mental Distress In The mentioning
confidence: 99%
“…Separation from the infant and the interruption of the relationship between parents and newborns contribute to aggravating the already weakened family emotional state, which is commonly manifested by acute anxiety (23); Correia, Rocha & Dittz, 2019). A high stress score is also associated with a higher level of depressive symptoms (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…The review by Mannava et al (2015) showed that attitudes and behaviors of maternal health-care providers can affect patients' well-being, satisfaction with care, and care seeking. Mendelson et al's (2017) review showed that the trauma-focused cognitive behavioral therapy (CBT) and education adapted from COPE program and problemsolving education based on CBT achieves significantly reduced maternal depressive but not anxiety symptoms.…”
Section: What Disturbs Women's Psychological Well-being and Emotionmentioning
confidence: 99%